Promised land : how the rise of the middle class transformed America, 1929-1968 - Stebenne, David (Scribner, 2020)
"A timely work of groundbreaking history explains how the American middle class ballooned at mid-century until it dominated the nation, showing who benefited and what brought the expansion to an end"--